A New Approach to Simplifying Boolean Functions - A. H. M. Ashfak Habib; Md. Abdus Salam; Zia Nadir; Hemen Goswami (The Journal of Engineering Research, 2004)
There are many benefits to simplifying Boolean functions before they are implemented in hardware. A reduced number of gates decreases considerably the cost of the hardware, reduces the heat generated by the chip and, most importantly, increases the speed. But no method is effective for the simplification of Boolean functions, if it involves more than six variables. This paper presents a new manual method of simplification that can be effectively applied to problems with a large number of variables.